Shake the devil off [compact disc, unabridged] : a true story of the murder that rocked New Orleans - Brown, Ethan, 1972- (Phoenix Audio, 2009)
NYC journalist Ethan Brown investigates the tragic end of Zackery Bowen, a young charismatic soldier from New Orleans, and his girlfriend, Addie Hall, in this moving and mesmerizing account of the war in Iraq, Hurricane Katrina, and no-safety-net America. Among the newsworthy elements in the book is Brown's discovery that this tragedy--like so many others--could have been avoided if the military had simply not failed this soldier.